Gospodarsko sodelovanje afriških držav s Kitajsko - Vintar Mally, Katja (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2013)
The paper focuses on the main characteristics and the latest trends in China%s economic co-operation with Africa, especially regarding the geographical implications of trade volume and structure, foreign direct investment, and development assistance. The second part of the paper presents key findings of empirical research in Angola, highlighting Angolan perception of economic ties to China as well as attitudes towards Chinese immigrants and their role in African society and economy.
Keywords: Africa; Afrika; Angola; ekonomska geografija; investicije; Kitajska; mednarodno ekonomsko sodelovanje